EFFECTS OF IMMMUNITY AND DRUGS RESISTANCE ON THE TRANSMISSION DYNAMICS OF TUBERCULOSIS - S. I. KAMARA; E. E. TANTO; A. SANDA; A. AUDU; CHAJIRE P. B (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
SIER epidemiology model was modified to determine the effect of drug resistance and immunity on the transmission dynamics of tuberculosis. We obtained the existence and uniqueness of the solution of the model, the basic reproduction number . The disease-free equilibrium point was determined and found to be locally asymptotically stable (LAS), when and globally asymptotically stable (GAS), when unstable if otherwise. The endemic equilibrium was also obtained and found to be locally asymptotically stable (LAS) when and globally asymptotically stable (GAS), when . Numerical simulation carried out shows that there is less infected population with the first line of treatment when there is no drug resistance.